Resilience, Gender, Self-efficacy, and Emotion Maturity among Gen Z: Correlation Model and Mapping - Pratama, Rio Candra (Universitas Mercu Buana Jakarta, 2025)
Resilience, the capacity to adapt and recover from adversity, is increasingly relevant for understanding Generation Z, often described as the “strawberry generation” for their perceived fragility. Empirical evidence on the determinants of resilience in this cohort, however, remains limited. This study examined the influence of gender, self-efficacy, and emotional maturity on resilience among Indonesian Gen Z. A cross-sectional survey was conducted with purposive sampling of 580 respondents from Java Island. Correlation analysis revealed significant associations between resilience and gender, self-efficacy, and emotional maturity. Further regression analysis indicated that only self-efficacy and emotional maturity significantly predicted resilience, while gender did not. Geospatial mapping showed regional variation, with East Java reporting the highest resilience scores and Central Java the lowest. The findings underscore the importance of self-efficacy and emotional maturity in fostering resilience, whereas gender differences appear negligible. The study is limited by its reliance on standardized group categorization of resilience. Future research should refine measurement approaches and investigate regional variations in self-efficacy and emotional maturity to provide a more nuanced understanding of Gen Z’s adaptive capacity.